Radioiodine Treatment and The Development of Pretibial Myxedema: A Series of Three Cases - Perini, Nicolas; Rossi, Camila Guidi; Martinez, Gabriela Salles; Rojas, Yedda Carolina Della Torre; Santos, Roberto Bernardo; Hamilton Romaldini, João; Villagelin, Danilo (Brazilian Journal of Case Reports, 2025)
Graves’ disease presents itself clinically with signs of hyperthyroidism and autoimmune manifestations like Graves’ dermopathy, mainly the pretibial myxedema, treatment for Graves’ disease relies on the use of antithyroid medications and radioiodine treatment (RAI) in which case the thyroid cell destruction and subsequent antigen release aggravates the autoimmune response leading to TRAb mediated mucin and glycosaminoglycan deposition in the pretibial area. This report presents 3 cases of pretibial myxedema after radioiodine treatment for Graves’ Disease combined with a brief literature review. This paper suggests that Graves’ dermopathy could be due to an exacerbation of thyroid autoimmunity after RAI treatment. Physicians and patients' awareness of skin complaints or alterations play a key role in early diagnosis and treatment.